A Qualitative Study on the Role of Leaders’ Mindfulness on Corporate Social Responsibility in Pakistani Industries - Abbas, Rameesha (Archives of Business Research, 2023)
Not altogether unlike CSR, an in-depth background study provides less than a clear and concise definition of mindfulness leadership; nevertheless. Although an economic and social case for adopting CSR has clearly emerged, many organizations and leaders are finding it challenging to establish meaningful and sustainable CSR policies and practices. Hence, by investigating the top-management expertise in designing and implementing CSR initiatives among small and medium enterprises are important concepts to explore. The primary data was collected qualitatively using personal interviews with 28 top-management level employees working in different SMEs of Pakistan. The results found that leaders’ mindfulness is important at all levels from designing to execution of CSR initiatives to achieve desire results such as sustained competitive advantage and along with community development. This study provides researchers an opportunity to gain understanding as to the application of mindfulness leadership as an effective framework for organizations to better achieve their social responsibility goals.